The game animator's guide to Maya - McKinley, Michael (Wiley Publishing, 2006)
The Ultimate Resource for Professional Game Animators Game animation is a demanding art. Not only do you have to deliver realistic, beautiful animations, but you have to do so under strict real-time, video-game constraints.